Metamaterial Transmission Line-for Designing a Microstrip Patch Antenna - Kr Kaushik, Awanish; Kumar, Anubhav; L. Yadava, R (International Journal of Engineering and Technology, 2018)
In this paper, the fundamental properties, limit and structure of metamaterial express that the "meta-transmission line (meta-TL) is utilized for solace implies metamaterial transmission lines are reasonably homogenous structures, which have properties that don't appear in regular transmission lines. It intertwines all the transmission line structures which have interesting properties not existing in ordinary RH-TL, for instance, LH TL, CRLH TL, SRR -stacked TL and further. As diverged from various materials, the Metamaterials are counterfeit metallic structures having meanwhile negative permittivity (É›) and vulnerability (Î¼), which prompts negative refractive summary. No other mate-rial on the planet demonstrates the above properties like Metamaterial. Because of these irregular properties Metamaterial can change the electric and attractive property of electromagnetic wave encountering it and in light of these reasons when Metamaterial is utilized as a bit of the make of microwave areas and radio wires the required properties can be refreshed.Â Â Â